IMPORTANCE OF THE DIRECTLY OBSERVED TREATMENT INTAKE ON THE APPROACH OF PATIENTS WITH RESISTANT HYPERTENSION. (June 2018) - Polonia, J.; Salgueiro, A.; Silva, J.; Barbosa, L.
Abstract : Objective: The diagnosis of resistant hypertension (HRes) and the efficacy of renal denervation ensure proper compliance with the therapy. We intend to assess the usefulness of directly observed treatment intake (OTI) in the control of adherence to anti-hypertensive medication in patients with HTAres. Figure. No caption available. Design and method: We studied 46 patients with Hres (BP>/ou 150 90 mm Hg under with at least 3 different classes of drugs in optimal doses) in outpatient hypertension clinic. Four were previously submitted to renal denervation. 24-h ambulatory BP (ABP) was evaluated before the procedure. In OTI patients took all medications in the morning for 5 days under the supervision of a technician and performing on the fifth day a second ABP. Results: Out of the 46 patients 76% were female, ageing 63 ± 11 years and BMI 30 ± 5 Kg/m2. The average of antihypertensive agents was 4.5 ± 1.2 /day. After OTI casual, daytime and nighttime BP decreased significantly (Table). After OTI, 16 patients (34.8%) reported adverse drug reactions not reported before, and 54.3% normalized ABP (24 h < 130/80 mm Hg). Also 4 patients who persisted with HRes after renal denervation were shown to be BP controlled after OTI. Conclusions: In an organized clinic, OTI can be performed, thereby becoming a valuable tool to identify the non-compliance to therapy as a cause of HRes and to identify false non-responders to techniques such as renal denervation due to loss of drug adherence.